Retheorizing Religion in Nepal - Grieve, G. author. aut Link
XIX, 172 p. 8 illus.
Keywords: Retheorizing Religion in Nepal is an engaging and thought-provoking study of Religion in South Asia, with important insights for the study of religion and culture more broadly conceived. Grieve uses ethnographic material as well as poststructuralist and postcolonialist approaches to critique and expand religious studies as a discipline.